Effect of microbial polysaccharides on the quality indicators of protein-free and gluten-free products during storage - Samokhvalova , Olga; Kucheruk , Zinoviya; Kasabova , Kateryna; Oliinyk , Svitlana; Shmatchenko , Nataliа (Eastern-European Journal of Enterprise Technologies, 2021)
This paper reports a study into the effect of the microbial polysaccharides (MPS) xampan, enposan, and gelan on quality indicators during the storage of protein-free bread and gluten-free muffins. Microbial polysaccharides such as xampan, enposan, and gelan are effective structure-forming agents in gluten-free products. These hydrocolloids not only participate in the formation of the structure of dough and finished products but also affect the staling processes in gluten-free products during storage. The addition of the studied MPS leads to a slowdown in the staling processes of protein-free bread based on corn starch, as well as muffins based on wheat germ meal, during storage. It was found that in 24 hours of storage, the protein-free bread demonstrates a decrease in the moisture loss and crumbling index, as well as an increase in compressibility indicator, compared with control samples. It was also determined that gluten-free muffins with the addition of MPS lose moisture more slowly over 7 days of storage; they have lower crumbling and compressibility indices compared to the control. This is due to the high hydrophilic properties of the studied microbial polysaccharides, which can bind a significant amount of water and retain it during the storage of products. In addition, microbial hydrocolloids can envelop the gelatinized starch grains with a thin film, thereby helping inhibit the process of starch retrogradation. The samples of bread and muffins containing MPS almost did not change their appearance, color, taste, and smell during the studied shelf life, while the crumb of the examined samples demonstrated better elasticity and less crumbling. All studied MPS exhibit the same nature of the effect on the quality indicators of products during storage with xampan exerting the greatest effect and gelan ‒ the least